2015
DOI: 10.3923/ppj.2015.212.222
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Compatible Plant Virus Interaction: A Case Study with Bunchy Top Virus-Banana Host-Pathosystem

Abstract: A B S T R A C TVirus infection can result in the alteration of physiological, biochemical and metabolic processes within plants leading to symptom development. Banana bunchy top virus (BBTV) is one of the most destructive viral diseases in Tropical Asia, Pacific Indian Oceania (PIO) regions and Africa leading to 100% yield loss in banana and plantains. Though molecular characterization and their diversity were studied in depth in recent years, information on physiological and biochemical changes during banana-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 68 publications
(69 reference statements)
8
18
0
Order By: Relevance
“…The infected genotypes did not attain maximum potentials particularly seed weight owing to impairment of the growth structures. This agrees with the findings of [33] who reported that various biochemical and physiological processes were compromised in Bunchy top virus-banana hostpathosystem. Viruses are obligate parasites that utilise their host resources including ribosomes and mitochondria for self-replication and establishment.…”
Section: Discussionsupporting
confidence: 93%
“…The infected genotypes did not attain maximum potentials particularly seed weight owing to impairment of the growth structures. This agrees with the findings of [33] who reported that various biochemical and physiological processes were compromised in Bunchy top virus-banana hostpathosystem. Viruses are obligate parasites that utilise their host resources including ribosomes and mitochondria for self-replication and establishment.…”
Section: Discussionsupporting
confidence: 93%
“…Our study suggests that sugars increase during BBTV infection may control photo inhibitory processes and produce symptoms. The Anuradha et al [21] was similar to the findings of our study where changes in the sugar and starch content were the same in all the banana cultivars viz., Virupakshi, Grand Naine and Rasthali. Viruses lter both their rate of synthesis and rate of translocation and have little effect on carbohydrates which affects the overall growth of…”
Section: Incidence On Thesupporting
confidence: 92%
“…6). In an earlier report, a similar increase in the activity of POX was observed in Virupakshi and Grand Naine cultivar [21]. The peroxidases ar whose primary function is to oxidize hydrogen donors at the expense of peroxides which is known to be involved in oxidative damage in response to stress to the plant.…”
Section: Peroxidasesupporting
confidence: 67%
See 2 more Smart Citations